Circumstantial Evidence in Criminal Proof: Is It Reliable? - Arifuddin Arifuddin; Hariman Satria; Faisal Abdaud (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Proof is the backbone of criminal justice. Because any party who lacks evidence will lose in the court decision. In current judicial practice in Indonesia, there is a lot of discussion about indirect evidence. This term originates from the common law criminal law doctrine and is starting to be used by Indonesian academics when explaining criminal cases in court. The results of the study show that normatively, the Criminal Procedure Code does not recognize the distribution of evidence, either direct or indirect. In criminal justice practice, indirect evidence can be seen in its functionalization in two decisions, namely decision Number 498K/PID/2017. Indirect evidence used is in the form of: witness statements, expert statements, letters and instructions. Furthermore, decision Number 1813K/PID.SUS/2016. The indirect evidence used is documentary evidence and statements from several witnesses. In order not to cause errors in practice, direct evidence must be prioritized, not the other way around.